(untitled) (Fiep Bulletin - online, 2017)
More modern methods of cardiac abnormalities detection are needed to better diagnosis of heart disease. Exercisecauses profound changes in the heart during exercise and after exercise because of the Poiseuille Law. The increased flowcauses reduced resistance in the walls of blood vessels sparing the heart of a larger effort to overcome the peripheral resistance.Mathematical methods like Detrended Fluctuations Analysis shows that exercise improves autocorrelation heart rhythmsmathematically proving the regulation of heart rate with the effort. In this way, you can lower blood pressure after exercise benefitto heart health.